Knowledge of xerostomia in the elderly in Rejosari Village, Lamongan Regency, East Java - Sukmawati, Natasya Fauzia; Ratna Fitri, Adinda; Radithia, Desiana; Parmadiati, Adiastuti Endah; Ayuningtyas, Nurina Febriyanti; Mahdani, Fatma Yasmin (Indonesian Journal of Dental Medicine, 2025)
Background: Xerostomia, or dry mouth, is a subjective sensation often linked to hyposalivation, affecting oral and overall health. With a global prevalence of 5.5% to 46%, it is more common in the elderly due to factors like polypharmacy, systemic diseases, and age-related salivary gland changes. Xerostomia impacts daily activities such as speaking, chewing, and swallowing, reducing quality of life. Rejosari Village in Lamongan Regency, East Java, has a high elderly population and a well-established healthcare center for seniors (Posyandu Lansia), making it an ideal setting for studying awareness and knowledge of xerostomia. Purpose: To describe the level of knowledge of xerostomia among elderly people in Rejosari Village, Lamongan Regency, East Java. Methods: This descriptive observational study utilized an online questionnaire distributed via Google Forms. Participants were selected through consecutive sampling, focusing on elderly individuals who met the inclusion criteria. Of the 75 respondents who completed the questionnaire, 70 were included in the final analysis. Data were analyzed descriptively, categorizing knowledge levels into high, moderate, and low. Results: Among the 70 eligible respondents, 70.00% exhibited a high level of knowledge about xerostomia. Meanwhile, 22.86% were classified as having moderate knowledge, and 7.14% had low knowledge levels. These findings indicate that most elderly residents in Rejosari Village are well-informed about xerostomia, although knowledge gaps persist among certain groups. Conclusion: The elderly’s knowledge about xerostomia in Rejosari Village, Lamongan Regency, East Java is dominated in the high knowledge category.